Response to Interleukin-17A Inhibitors According to Prior Biologic Exposures: A Danish Nationwide Study - Nikolai Loft; Alexander Egeberg; Daniel Isufi; Mads K. Rasmussen; Lars E. Bryld; Tomas N. Dam; Kawa K. Ajgeiy; Trine Bertelsen; Lone Skov (Medical Journals Sweden, 2023)
Whether response to an interleukin (IL-17) inhibitor is different in patients with previous exposure to an IL-17 inhibitor compared with patients with exposure to biologics with other cytokine targets remains to be elucidated. Therefore, the aim of this study was to  assess whether previous exposure to an IL-17A inhibitor was associated with worse response than exposure to (an)other biologic(s). All patients in the DERMBIO register treated with an IL-17A inhibitor (secukinumab or ixekizumab) were included. With an absolute Psoriasis Area and Severity Index (PASI) ≤ 2 as response, the proportion of responders treated with IL-17A inhibitors was assessed in patients previously treated with another IL-17A inhibitor and compared with patients with previous exposure to (an)other biologic(s), using a χ2 test. In total, 100, 93 and 83 patients with  previous exposure to an IL-17A inhibitor and 414, 372 and 314 patients with previous exposure to (an) other biologic(s) were assessed after 3, 6 and 12 months, respectively. No differences in the proportion of  patients achieving PASI ≤ 2 were observed between the 2 groups after 3 months (54% vs 57%, p = 0.59), 6months (70% vs 66%, p = 0.42) and 12 months (69% vs 60%, p = 0.14). In conclusion, when treating patients with IL-17A inhibitors the cytokine target of the previous biologic does not appear to affect the  response.